Amelia: A multi-center descriptive epidemiologic study in a large dataset from the International Clearinghouse for Birth Defects Surveillance and Research, and overview of the literature - Bermejo Sánchez, Eva (2011)
This study describes the epidemiology of congenital amelia (absence of limb/s), using the largest series of cases known to date. Data were gathered by 20 surveillance programs on congenital anomalies, all International Clearinghouse for Birth Defects Surveillance and Research members, from all continents but Africa, from 1968 to 2006, depending on the program. Reported clinical information on cases was thoroughly reviewed to identify those strictly meeting the definition of amelia. Those with amniotic bands or limb-body wall complex were excluded. The primary epidemiological analyses focused on isolated cases and those with multiple congenital anomalies (MCA). A total of 326 amelia cases were ascertained among 23,110,591 live births, stillbirths and (for some programs) elective terminations of pregnancy for fetal anomalies. The overall total prevalence was 1.41 per 100,000 (95% confidence interval: 1.26-1.57). Only China Beijing and Mexico RYVEMCE had total prevalences, which were significantly higher than this overall total prevalence. Some under-registration could influence the total prevalence in some programs. Liveborn cases represented 54.6% of total. Among monomelic cases (representing 65.2% of nonsyndromic amelia cases), both sides were equally involved, and the upper limbs (53.9%) were slightly more frequently affected. One of the most interesting findings was a higher prevalence of amelia among offspring of mothers younger than 20 years. Sixty-nine percent of the cases had MCA or syndromes. The most frequent defects associated with amelia were other types of musculoskeletal defects, intestinal, some renal and genital defects, oral clefts, defects of cardiac septa, and anencephaly.